Deep Brain Stimulation for Pantothenate Kinase-Associated Neurodegeneration - Pedro J. Garcia-Ruiz; Joaquin Ayerbe; Lydia Vela Desojo; Cici E. Feliz; Javier del Val Fernandez (Case Reports in Neurological Medicine)
Pantothenate kinase-associated neurodegeneration (PKAN) is usually associated with dystonia, which is typically severe and progressive over time. Pallidal stimulation (GPi DBS) has been carried out in selected cases of PKAN with drug-resistant dystonia with variable results. We report a 30-month follow-up study of a 30-year-old woman with PKAN-related dystonia treated with GPi DBS. Postoperatively, the benefit quickly became evident, as the patient exhibited a marked improvement in her dystonia, including her writing difficulty. This result has been maintained up to the present. GPi DBS should be considered in dystonic PKAN patients provided fixed contractures and/or pyramidal symptoms are not present.